The Game - Fincher, David, 1962-; Douglas, Mıchael, 1944-; Sean Penn; Deborah Kara Unger; James Rebhorn; Peter Donat; Carroll Baker; Anna Katarina; Armin MuellerStahl; Charles Martinet; Scott Hunter McGuire; Florentine Mocanu; et al. (USA A&B Producoes, Lda., 1997)
Wealthy financier Nicholas Van Orton gets a strange birthday present from wayward brother Conrad: a live-action game that consumes his life.
Nicholas Van Orton is a very wealthy San Francisco banker, but he is an absolute loner, even spending his birthday alone. In the year of his 48th birthday (the age his father committed suicide) his brother Conrad, who has gone long ago and surrendered to addictions of all kinds, suddenly returns and gives Nicholas a card giving him entry to unusual entertainment provided by something called Consumer Recreation Services (CRS). Giving up to curiosity, Nicholas visits CRS and all kinds of weird and bad things start to happen to him.
Players Wanted.
Language(s): English, Turkish Subtitle(s): Turkish
Keywords: Action; Adventure; Mystery; Thriller